Moliyaviy texnologiyalarning an’anaviy bank tizimiga ta’siri: imkoniyatlar va tahdidlar - Rustamov Jasurbek Ravshanbek o‘g‘li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The development of fintech is encouraging traditional banks to adopt digital technologies. Digital payments, artificial intelligence, and blockchain are helping to make services faster and more efficient. Banks can increase their competitiveness by collaborating with fintech and strengthening automation and cybersecurity. The use of modern technologies will serve as a basis for sustainable growth of banks.